(3JejjR GdWjH ef GdNHjK eeG jOhQ Ydi CdSfI GdfGS ef GdMOjKs - (3CHh GdVjGA YHO GdQMef Hf Ydj Hf eMeO GdTjHGfj GdRHjOj GdTGaYj GHf GdOjHY, GHf GdOjHY,J (B944 (3g` s
(3ChdgG (B:s
(3CeG HYO aEfi bO hbYJ Ydi cJGH GdebGUO GdMSfI ai HjGf GdCMGOjK GdOGFQI Ydi GdCdSfI dTjNfG GdSNGhi dcfg CWGdg aLQOJ ai gPG GdeNJUQ ahGFOg hLYdJg Ydi GdMQha JHYG dCUdg s
(3BNQgG (B:s
(3bGd eNJUQg aQZJ ef GNJUGQg VMi jhe GdNejS GdKGfi YTQ ef QeVGfq s
(3Vef eLehY , JQJjHgG (B: 13s
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfS HJGQjN (B1256 (3g`s
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B485s
Keywords: (3GdMOjK h GdeUWdMs